Influence of dosimetric and clinical criteria on the requirement of artificial nutrition during radiotherapy of head and neck cancer patients. Issue 1 (July 2016) - Matuschek, Christiane; Bölke, Edwin; Geigis, Caroline; Kammers, Kai; Ganswindt, Ute; Scheckenbach, Kathrin; Gripp, Stephan; Simiantonakis, Jannis; Hoffmann, Thomas K.; Greve, Jens; Gerber, Peter Arne; Orth, Klaus; et al.
Abstract: Purpose/objective(s): Intensification of radiotherapy and chemotherapy for head-and-neck cancer (HNC) may lead to increased rates of long term dysphagia as a severe side effect. Mucositis and consequent swallowing problems require artificial nutrition in many HNC patients undergoing radiotherapy or chemoradiation. It is unknown, which predict factors for prophylactic PEG tube insertion appear useful. Materials/methods: From an institutional database, 101 patients (72 male, 29 female, mean age 59.5 years) were identified who underwent radiotherapy or chemoradiation for HNC. Primary end point of the investigation was the need for artificial nutrition for more than 4 days during radiotherapy. Dose volume parameters of defined normal tissue structures potentially of relevance for swallowing ability as well as clinical factors were used to develop a predictive model using a binary multiple logistic regression model. Results: Whereas several dosimetric and clinical factors were significant predictors for the need of artificial nutrition on univariate analysis, on multivariate analysis only three factors remained independently significant: mean dose to the oropharynx + 1 cm circumferential margin, ECOG performance state (0–1 vs. 2–4), and the use of chemotherapy (yes vs. no). Conclusions: Using a 3 parameter model we could distinguish HNC-patients with different risks for the need of artificial nutrition during radiotherapy. After independent validation, the model could be helpful to decision on prophylactic PEG tube insertion.